1
$\begingroup$

For $\alpha>0,\lambda>0$, I am trying to evaluate the integral

$$I(\alpha,\lambda)=\int_{\mathbb R}\frac{e^{-\alpha y}}{(1+e^{-y})^{1+\lambda}}\,\mathrm{d}y$$

Basically I am struggling to find a proper substitution here.

I can write

$$I(\alpha,\lambda)=\int_{\mathbb R}e^{(1-\alpha)y}\frac{e^{-y}}{(1+e^{-y})^{1+\lambda}}\,\mathrm{d}y$$

Changing variables $$z=\frac{1}{(1+e^{-y})^{(1+\lambda)/2}}$$

, so that $$\mathrm{d}z=\left(\frac{1+\lambda}{2}\right)(1+e^{-y})^{\frac{\lambda-1}{\lambda+1}}\frac{e^{-y}}{(1+e^{-y})^{1+\lambda}}\,\mathrm{d}y\tag{1}$$

Now,

\begin{align} &\qquad\quad z(1+e^{-y})^{(1+\lambda)/2}=1 \\&\implies \ln z+\left(\frac{1+\lambda}{2}\right)\ln(1+e^{-y})=0 \\&\implies \ln(1+e^{-y})=-\frac{2}{1+\lambda}\ln z \\&\implies e^{-y}=\exp\left(-\frac{2}{1+\lambda}\ln z\right)-1=z^{-2/(1+\lambda)}-1 \end{align}

From $(1)$, I get $$\frac{e^{-y}}{(1+e^{-y})^{1+\lambda}}\,\mathrm{d}y=\left(\frac{2}{1+\lambda}\right)z^{\frac{\lambda-1}{\lambda+1}}\,\mathrm{d}z$$

And

$$e^{(1-\alpha)y}=(e^{-y})^{-(1-\alpha)}=\left(z^{-2/(1+\lambda)}-1\right)^{\alpha-1}$$

So finally,

$$I(\alpha,\lambda)=\frac{2}{1+\lambda}\int_0^1 \left(z^{-2/(1+\lambda)}-1\right)^{\alpha-1}z^{\frac{\lambda-1}{\lambda+1}}\,\mathrm{d}z$$

I transformed the domain of integration to $(0,1)$ so that I can use the Beta function and hence get an answer in terms of Gamma functions. But looks like I have made an error somewhere.


I also tried writing $$\frac{1}{(1+e^{-y})^{1+\lambda}}=\sum_{j=0}^\infty \binom{-(1+\lambda)}{j}e^{-yj}$$

, so that

\begin{align} I(\alpha,\lambda)&=\int_{\mathbb R} e^{-\alpha y}\sum_{j=0}^\infty \binom{-(1+\lambda)}{j}e^{-yj}\,\mathrm{d}y \\&\stackrel{?}{=}\sum_{j=0}^\infty \binom{-(1+\lambda)}{j}\int_{\mathbb R}e^{-(\alpha+j)y}\,\mathrm{d}y \end{align}

But this is not correct either.


According to Mathematica, I should get

$$I(\alpha,\lambda)=\frac{\Gamma(\alpha)\Gamma(1+\lambda-\alpha)}{\Gamma(1+\lambda)}\quad,\text{ if }\alpha<1+\lambda$$

$\endgroup$
4
$\begingroup$

You can use $x = \frac{1}{1+\mathrm{e}^{-y}} ~ \Leftrightarrow ~ \mathrm{e}^{-y} = \frac{1-x}{x}$ here. Then $$ I(\alpha, \lambda) = \int \limits_0^1 x^{\lambda-\alpha} (1-x)^{\alpha-1} \, \mathrm{d} x = \operatorname{B} (1+\lambda-\alpha,\alpha) = \frac{\Gamma(\alpha) \Gamma(1+\lambda-\alpha)}{\Gamma(1+\lambda)} \, . $$

$\endgroup$
  • $\begingroup$ Thanks, it was the simple substitution that I ignored. $\endgroup$ – StubbornAtom Nov 2 '18 at 12:13

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.